Scatter rejection and low-contrast performance of a slot-scan digital chest radiography system with electronic aft-collimation: A chest phantom study - Liu, Xinming (American Association of Physicists in Medicine, 2008)
Anti-scatter grids have been widely used to reject scatter and increase the perceptibility of low-contrast object in chest radiography; however they also attenuate the primary x-rays, resulting in a substantial degradation of primary information. Compensation for this degradation requires the use of higher exposure technique hence higher dose to the patient. A more efficient approach to reject scatter is the slot-scan imaging technique which employs a narrow scanning x-ray fan beam in conjunction with a slit or slot shaped solid state detector or an area detector used with an aft-collimator. With this approach, scatter can be rejected effectively without the need to attenuate primary x-rays. This paper demonstrates an electronic aft-collimation method, referred to as the alternate line erasure and readout (ALER) technique, for implementing the slot-scan digital radiography with a modern flat-panel detector. With this technique, instead of first exposing the detector and then reading the image line by line, the image line on the leading edge of the scanning fan beam is reset to erase the scatter accumulated prior to the arrival of the fan beam x-rays, while the image line on the trailing edge of the scanning fan beam is read out to acquire the image signals following the fan-beam exposure. These reset and readout processes are alternated and repeated as the x-ray fan beam scans across the detector. An anthropomorphic chest phantom was imaged to evaluate the scatter rejection ability and the low-contrast performance for the ALER technique and compare them with those for the anti-scatter grid method in full-field chest imaging. With a projected beam width of 16 mm, the slot-scan∕ALER technique resulted in an average reduction of the scatter-to-primary ratios by 81%, 84%, 82%, and 86% versus 65%, 73%, 74%, and 73% with the anti-scatter grid method in the lungs, mediastinum, retrocardium, and subdiaphragm, respectively. The average CNR for the slot-scan∕ALER technique was found to improve by 135%, 133%, 176%, and 87% versus 15%, 15%, 38%, and −11% with the anti-scatter grid method in the mediastinum, retrocardium, subdiaphragm, and lungs, respectively. These results demonstrated that the slot-scan∕ALER technique can be used to achieve equally effective scatter rejection but substantially higher low-contrast performance than the anti-scatter grid method.